A comparative study of sports injuries in physical education lessons (Journal of the College of Basic Education, 2022)
The research is a survey field study aimed at a comparative study of sports injuries in physical education lessons, their causes and locations, and the activities that occurred in them for students of the College of Basic Education / Department of Physical Education / Al-Mustansiriya University. bug.